Răspuns :
a|----| +9
b|----|
a-b =9
3a+3b = 363
a=b+9
3(b+9)+3b =363
3b+27+3b =363
6b +27=363
6b =363-27
6b = 336
b=336:6
b=56
a=b+9= 56+9= 65
b|----|
a-b =9
3a+3b = 363
a=b+9
3(b+9)+3b =363
3b+27+3b =363
6b +27=363
6b =363-27
6b = 336
b=336:6
b=56
a=b+9= 56+9= 65
a. |----------| + 9
b. |----------|
|----------|----------|----------|----------|---------|---------| + 27 = 3a + 3b = 363
3a + 3b = 363
a - b = 9 => a = b + 9 ; b = a - 9
a, b = ?
3 ( b + 9 ) + 3b = 363
3b + 27 + 3b = 363
6b = 363 - 27
6b = 336 : 6
b = 56 => a = 56 + 9 => a = 65
b. |----------|
|----------|----------|----------|----------|---------|---------| + 27 = 3a + 3b = 363
3a + 3b = 363
a - b = 9 => a = b + 9 ; b = a - 9
a, b = ?
3 ( b + 9 ) + 3b = 363
3b + 27 + 3b = 363
6b = 363 - 27
6b = 336 : 6
b = 56 => a = 56 + 9 => a = 65